Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.4269/ajtmh.2012.11-0515
|View full text |Cite
|
Sign up to set email alerts
|

Landscape-Level Spatial Patterns of West Nile Virus Risk in the Northern Great Plains

Abstract: Abstract. Understanding the landscape-level determinants of West Nile virus (WNV) can aid in mapping high-risk areas and enhance disease control and prevention efforts. This study analyzed the spatial patterns of human WNV cases in three areas in South Dakota during [2003][2004][2005][2006][2007] and investigated the influences of land cover, hydrology, soils, irrigation, and elevation by using case-control models. Land cover, hydrology, soils, and elevation all influenced WNV risk, although the main drivers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…One study in Georgia found birds in forested habitats showing WNV seroprevalence at levels nearly as high as birds from urban and suburban sites (Gibbs et al 2006b), whereas another identified a larger proportion of urban tree cover as significant factor in WNV infection spatial clusters (Vazquez Prokopec et al 2010). A study from South Dakota even identified forests as a factor contributing to a positive association with WNV risk (Chuang et al 2012). Increased vegetation levels, especially in urban areas, provide optimal habitats for avian hosts of WNV and facilitate contact between bird species that congregate in these areas, thereby aiding in transmission amplification (Messina et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…One study in Georgia found birds in forested habitats showing WNV seroprevalence at levels nearly as high as birds from urban and suburban sites (Gibbs et al 2006b), whereas another identified a larger proportion of urban tree cover as significant factor in WNV infection spatial clusters (Vazquez Prokopec et al 2010). A study from South Dakota even identified forests as a factor contributing to a positive association with WNV risk (Chuang et al 2012). Increased vegetation levels, especially in urban areas, provide optimal habitats for avian hosts of WNV and facilitate contact between bird species that congregate in these areas, thereby aiding in transmission amplification (Messina et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the percentage of wetland is not associated with the abundance of Cx. tarsalis and WNV risk in the Canadian prairies and northern Great Plains [13,14,17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…Aedes vexans Meigen is a nuisance mosquito and can potentially serve as a bridge vector of WNV (Turell et al, 2005). Previous research has highlighted the importance of the Northern Great Plains as a region of consistently high WNV risk and quantified influences of climate and land cover on spatial patterns of WNV risk (Chuang et al, 2012; Wimberly et al, 2008). Meteorological variables measured using weather stations have also been identified as important drivers of mosquito abundance, with Cx.…”
Section: Introductionmentioning
confidence: 99%